Prevalence and factors associated with low back pain in elderly registered in the Family Health Strategy - Natasha Mendonça Quintino; Marta Helena Souza De Conti; Roger Palma; Márcia Aparecida Nuevo Gatti; Sandra Fiorelli Almeida Penteado Simeão; Alberto De Vitta
Abstract Introduction: Low back pain has varied etiology and complex discussed and can be triggered by various factors. Objective: Was to assess the prevalence of low back pain in individuals 60 years or more of the areas of the Family Health Strategy "Vila Sao Paulo" in the city of Bauru, São Paulo, and its association with demographic and socioeconomic variables, relating to work, lifestyle and morbidity. Methods: We conducted a cross-sectional study with 363 elderly sampled by the technique of two-stage cluster, which were interviewed at home using a multidimensional instrument (demographic, socio-economic, featuring work; lifestyle; morbidity) and the Nordic questionnaire. Conducted descriptive analysis, bivariate and Poisson regression. Results: It was noted more frequently in the elderly age group between 60 and 69 years old, married, with low education and income from two to five. The prevalence of low back pain was 55.8% of elderly patients studied, 52.2% in men and 47.8% women and, the variables load and carry weight (p = 0.001) and the number of diseases referred to (p = 0.04) showed association with the presence of low back pain. Conclusion: The elderly respondents show a high prevalence of low back pain associated with the loading and transport weight and the number of diseases referred.